2003
DOI: 10.1212/01.wnl.0000052992.58107.67
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of nursing home placement in Huntington disease

Abstract: Institutionalized patients with HD are more motorically, psychiatrically, and behaviorally impaired than their counterparts living at home. However, motor variables alone predicted institutionalization. Treatment strategies that delay the progression of motor dysfunction in HD may postpone the need for institutionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 16 publications
2
98
1
1
Order By: Relevance
“…Accurate and responsive measurement of mobility and balance is very important because such impairments predict long-term care placement in HD [2]. While quantitative gait measures have been shown to be accurate and reliable in HD [8], they are not easy to administer in community-based studies due to lack of availability of expensive laboratory equipment at clinical facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate and responsive measurement of mobility and balance is very important because such impairments predict long-term care placement in HD [2]. While quantitative gait measures have been shown to be accurate and reliable in HD [8], they are not easy to administer in community-based studies due to lack of availability of expensive laboratory equipment at clinical facilities.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of HD patients would require long-term care during the course of the disease, and they are frequently admitted to the nursing homes until their deaths. Wheelock et al [20] found that patients in skilled nursing facilities had a longer duration of HD, and that more female than male HD patients resided the nursing homes. However, this explanation was not applicable in this study since families took care for majority of our patients (70% and 73% of male and female patients, respectively) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Care could be provided at home for most of the patients: only 2 patients required institutionalization. Motor symptoms (marked chorea, 33 bradykinesia, and impaired gait and balance 42 ), rather than psychiatric symptoms, have been shown to be predictors of nursing home placement in HD.…”
Section: -22mentioning
confidence: 99%